Plastyczne Wyczerpanie Nośności Ustrojów Płytowo-Żebrowych. Cz. 2. Rozwiązania Statyczne. - Kwieciński, M. (Engineering Transactions, 1963)
This is the second part of a work of which the first part appeared in Rozprawy Inzynierskie, where the problem of exhaustion of the load carrying capacity of a bent ribbed plate structures was analysed for a kinematically admissible field of strain increments. The upper bound of the real collapse load was found for ten types of ribbed structures. In the present paper the lower bound of the collapse load is found, bearing in mind the statically admissible field of internal forces and introducing the so-called rectangular yield condition. Plastic orthotropy and the layered character of the structure is taken into consideration. Solutions obtained by the static method are compared with those obtained by the kinematic approach. From the engineering view point the results of both methods differ but little. This fact may furnish a basis for the establishment of uniform criteria assuring uniform strength in all theelements of a ribbed plate structure.